Changes in Soil Physical Quality of Post-Coal Mining After Revegetation of Eucalyptus Plants (Melaleuca cajuputi) - Evira Khairunisa Putri; Bambang Sulistyo; Bandi Hermawan; Vinni Lovita; Esi Asyani Listyowati (Department of Soil Science, Faculty of Agriculture, University of Bengkulu, 2022)
Coal mining in Indonesia is generally carried out by open-pit mines so which impacts the decline of environmental quality degradation and damage to the soil’s physical properties. One of the steps taken by PT Bukit Asam Tbk to solve this problem is to carry out land reclamation by using eucalyptus plants. This study aims to of the revegetation age of eucalyptus plants on changes in the soil’s physical properties of post-coal mines. This research was carried out from October to December 2021 on post-coal mining land after the revegetation of eucalyptus plants for 3 years, 5 years, and 10 years in Pit Banko Barat, PT Bukit Asam Tbk. At the research location measurements and sampling were taken and followed by analysis at the Soil Science Laboratory, Bengkulu University. The data obtained were analyzed by descriptive statistics and normality test then continued analysis of variance and BNT test. The results showed that the age of eucalyptus plants has a significant effect and can improve soil density and root penetration at the age 5 and 10 years in post-coal mining land. The soil’s physical quality showed that soil bulk density, particle density, liquid limit, root penetration, groundwater level, as well as increased porosity and C-organic. It has the same texture that is clay and some changes in the blocky structure to be granular.